Physical Activity Space Methodology for Assessment and Prioritization (PASMAP): Combining systematic observations with community perceptions to identify community physical activity resource priorities. (November 2020) - Umstattd Meyer, M. Renée; Ylitalo, Kelly R.; Prochnow, Tyler; Gómez, Luis A.; Sharkey, Joseph R.
Abstract: Despite benefits of physical activity (PA), most Americans are not regularly active, with notable disparities for residents of low-income communities. PA is positively correlated with resource availability and quality, which can be measured and quantified by PA resource assessment tools. However, community members' perceptions are often not considered. This study incorporates community perceptions with systematic environmental observations to identify community PA resource priorities. The PA Space Methodology for Assessment and Prioritization (PASMAP) includes three phases. Phase 1: Promotora- researchers completed 57 PA Resource Assessments (PARAs) in colonias along the Texas-Mexico border assessing quantity and quality of features, amenities, and incivilities. Characteristics were ranked using average PARA scores from all PA spaces. Phase 2: community advisory board (CAB) members (n = 36 from 3 CABs) ranked the importance of each feature, amenity, and incivility respectively; rankings were averaged and ordered. Phase 3: differences between phases 1 and 2 were calculated. Large differences indicated high discordance between systematic observations and perceived importance. Phase 1: highest ranked PARA characteristics were sidewalks, non-street lighting, and noise. Phase 2: CAB members ranked trails/paths, sidewalks, play equipment, bathrooms, drinking fountains, substance abuse evidence, and litter most important. Phase 3: multiple characteristics had high discordance: trails/paths, fenced-in open fields (features), drinking fountains (amenity), and litter (incivility); low quantity/poor quality yet perceived as highly important. Discordant characteristics identified through PASMAP provide evidence-based, community-valued recommendations on PA resource priorities for planning and advocacy. Future work should incorporate perceptions from additional community members and apply PASMAP methods to other environmental assessments. Highlights: There was high discordance between some rankings and observations (low quantity/poor quality, high perceived importance). Discordant characteristics provide evidence-based, community-valued recommendations on PA resource priorities for planning. Future work should incorporate additional community members and apply PASMAP methods to other environmental assessments.